Improving follow-up visits among individuals with hypertension: Quality Improvement project in the District Hospital, Seoni, Madhya Pradesh, India, 2021–2022 - Prabhdeep Kaur; Rupali Bharadwaj; Mogan Kaviprawin; Namita Neelkanth; Vinod Kumar Navkar; Mohamed Jainul Azarudeen; Ganeshkumar Parasuraman; Archana Ramalingam (BMJ Open Quality)
Background In India, to achieve a 25% relative reduction in the prevalence of raised blood pressure (BP) by 2025, approximately 4.5 crore additional people with hypertension will need to have their BP effectively treated. We conducted a Quality Improvement (QI) initiative to improve follow-up and reduce missed visits among individuals with hypertension registered under India Hypertension Control Initiative, District Hospital, Seoni, Madhya Pradesh, India, in 2022.Methods We conducted a quasiexperimental study from January to September 2022 in the District Hospital in Seoni, Madhya Pradesh. Following the Ishikawa diagram, the major root causes for missed visits were identified, and countermeasures were developed. The packages under Plan-Do-Study-Act (PDSA) included (i) training urban Accredited Social Health Activists to conduct house visits for individuals with missed visits and (ii) triangulating the follow-up records from various information systems. The review meetings for QI initiatives were conducted fortnightly to follow-up PDSAs. We calculated the proportion of individuals who were followed-up monthly, and the proportion of missed visits among those registered quarterly.Results Cumulatively, 2850 individuals were registered with hypertension till September 2022. Following the intervention, the monthly follow-up proportion increased from 21% in January to 37% in September 2022. Missed visit proportion decreased from 66% (228/345) in quarter four, 2021, to 22% (40/180) in quarter three, 2022. Of the 1438 individuals counselled by ASHA home visits, 74.9% returned for follow-up.Conclusion In our setting, QI initiatives suggested that missed visits decreased during the intervention period. However, the interventions must be implemented continuously for better monitoring and use in similar settings.